2019
DOI: 10.1002/adfm.201903086
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Emission in Heteroepitaxial Ln‐SURMOFs

Abstract: By using a layer‐by‐layer (LbL) approach, lanthanide‐based, monolithic metal–organic framework (MOF) thin films are fabricated for optical applications. In particular, the LbL approach allows manufacturing of heteroepitaxial Tb(III)‐Eu(III)(BTC) coatings with precise thickness control. Adjusting the Tb(III)‐to‐Eu(III) ratio allows tuning of the emission color. The hetero‐multilayer architecture makes it possible to suppress the direct Tb(III)‐to‐Eu(III) energy transfer, an unwanted phenomenon present in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…[174] Particularly interesting, with regard to realizing mixed-metal MOFs, are lanthanide-based SURMOFs, since the very similar coordination chemistry of these metal ions allows switching between the different elements without pronounced changes of the MOF structure. [175] Figure 11. Layer-by-layer growth of a HKUST-I SURMOF on a quartzcrystal microbalance (QCM) crystal.…”
Section: Methodsmentioning
confidence: 99%
“…[174] Particularly interesting, with regard to realizing mixed-metal MOFs, are lanthanide-based SURMOFs, since the very similar coordination chemistry of these metal ions allows switching between the different elements without pronounced changes of the MOF structure. [175] Figure 11. Layer-by-layer growth of a HKUST-I SURMOF on a quartzcrystal microbalance (QCM) crystal.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, one would expect that the structural parameters of a Ln-based MOF would vary only a little when using a different lanthanide. Redel and coworkers recently demonstrated that, indeed, this approach enables the heteroepitaxy of Ln-based SURMOFs to be realized in a straightforward fashion [54].…”
Section: Heteroepitaxial Mof-on-mof Thin Films: Photophysical Propertiesmentioning
confidence: 99%
“…[176] Particularly interesting, with regard to realizing mixed-metal MOFs, are lanthanide-based SURMOFs, since the very similar coordination chemistry of these metal ions allows switching between the different elements without pronounced changes of the MOF structure. [177] Crystalline framework materials offer an additional means for functionality design: controlled van-der-Waals stacks of aromatic building blocks are subject to the proximity effect and raise phenomena such as wide absorption bands, mobile charge carriers, or indirect band gaps. Such stacks are present in layered MOFs and COFs, and can be created via steric control in 3D frameworks.…”
Section: Dftbmentioning
confidence: 99%